Analysis of Fairness Distribution of Capitation Service Between Health Centers - Dayyana, Latanza Shima; Gani, Ascobat (Journal of Economics and Public Health, 2022)
This article discusses the analysis of fairness distribution of capitation services between health centers in Bogor 2019. Objective: to conduct a fairness analysis of distribution of capitation service between health centers in Bogor 2019. Method: This research is a qualitative study with a case study design. The Population of this study was all workers in 101 health centers in Bogor, the sample was selected using Purposive Random Sampling and 5 health centers were selected, that is Tajur Halang, Leuwiliang, Cirimekar, Parung Panjang and Bojong. The data in this study were obtained from in-dept interviews with 18 informants, capitation data in 2017, 2018 and data on the realization of distribution capitation services at health center based on the regulation the Minister of Health Number 21 of 2016. The data is processed by going through several stages, that is data reduction, data display dan conclusion drawing. Results: The study show that there is external injustice related to services in capitation fund of Bogor district in 2019. Conclusions: There is a need for further research related to risk adjustment based on age, gender and geography to determine the amount of capitation between health centers. This research contributes to reviewing the establishment of Civil Servants Income Allowances, so that there is no disparity between health centers.